2021
DOI: 10.3389/fneur.2021.606673
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Smartphone Application to Speed Up Interhospital Transfer of Acute Ischemic Stroke Patients for Thrombectomy

Abstract: Background: In most countries, large cerebral artery occlusion is identified as the leading cause of disability. In 2015, five large-scale clinical trials confirmed the benefit of intra-arterial thrombectomy. However, thrombectomy is a highly technical and facility-dependent procedure. Primary stroke centers need to transfer patients to comprehensive stroke centers to perform thrombectomy. The time-lapse during interhospital transfer would decrease the chance of the patient's proper recovery. Communication bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This issue can be addressed from various perspectives, such as employing communication tools to facilitate information exchange between hospitals, expediting patient assessment after transfer, and accelerating subsequent time metrics. 20,21 Flying EST teams to remote areas can also help overcome the challenge of limited access to acute stroke care, leading to better outcomes for patients. 22 Moreover, reducing unnecessary referrals is an important hurdle to overcome.…”
Section: Discussionmentioning
confidence: 99%
“…This issue can be addressed from various perspectives, such as employing communication tools to facilitate information exchange between hospitals, expediting patient assessment after transfer, and accelerating subsequent time metrics. 20,21 Flying EST teams to remote areas can also help overcome the challenge of limited access to acute stroke care, leading to better outcomes for patients. 22 Moreover, reducing unnecessary referrals is an important hurdle to overcome.…”
Section: Discussionmentioning
confidence: 99%
“…32 A Taiwanese retrospective study on a smartphone application for interhospital transfer in thrombectomy for large vessel occlusion (LVO) acute ischemic strokes (AIS) showed a decrease in door-to-puncture time from 109.3 to 92 minutes over three years ( p = .045), with increased thrombectomy cases. 35 A Brazilian study supported the efficacy of a similar app, suggesting timely data review can be as accurate as the physical presence of stroke experts. 36 A review by Bonura et al found mobile apps beneficial in stroke care but highlighted a need for more interactive systems for clinicians in primary prevention, acute management and post-acute stroke care.…”
Section: Collaboration For Improved Stroke Carementioning
confidence: 92%
“…The China Medical University Hospital (CMUH) is located in central Taiwan and has a 2054-bed capacity. The stroke center treats approximately 1300 acute ischemic stroke patients and performs 90 tissue plasminogen activator (tPA) thrombolysis procedures and 120 intra-arterial thrombectomies annually[ 12 ].…”
Section: Methodsmentioning
confidence: 99%